2021
DOI: 10.3390/ijms22073721
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Muscle Cell Aging on Myogenesis

Abstract: The process of myogenesis gradually deteriorates as the skeletal muscle ages, contributing to muscle mass loss. The aim of this study is to investigate the effect of senescence/aging on skeletal myogenesis, in vitro. A model of multiple cell divisions of C2C12 myoblasts was used to replicate cell senescence. Control and aged myoblasts were investigated during myogenesis, i.e., at days 0, 2, and 6of differentiation. SA-β-gal activity and comet assay were used as markers of aging and DNA damage. Flow cytometry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 78 publications
(47 reference statements)
0
31
0
Order By: Relevance
“…The C2C12 cell line derived from murine skeletal muscle is an established model used to investigate muscle differentiation [ 33 , 34 , 35 ]. To identify how HY7715 induces muscle myogenic activation, C2C12 cells were differentiated for 5 days, and HY7715 was added to the differentiation media for the last 48 h. Whole-cell extracts of HY7715 were lysed, and the cytoplasmic and membrane fractions were isolated.…”
Section: Resultsmentioning
confidence: 99%
“…The C2C12 cell line derived from murine skeletal muscle is an established model used to investigate muscle differentiation [ 33 , 34 , 35 ]. To identify how HY7715 induces muscle myogenic activation, C2C12 cells were differentiated for 5 days, and HY7715 was added to the differentiation media for the last 48 h. Whole-cell extracts of HY7715 were lysed, and the cytoplasmic and membrane fractions were isolated.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, skeletal muscle tissue from older women (65–71 years old) expresses higher levels of CDKN1A than skeletal tissue from young women (20–29 years old) ( Welle et al, 2004 ). Several potential mechanisms of muscle cell senescence–mediated, aging-associated muscle loss (sarcopenia) were proposed based on an in vitro study using C2C12 cells, a murine myoblast cell line ( Alcalde-Estévez et al, 2020 ; Mijares et al, 2021 ; Moustogiannis et al, 2021 ). These studies revealed that elevated intracellular Ca 2+ concentration or endothelin-1 receptor in C2C12 cells induces cellular senescence, and senescent C2C12 cells increase the expression of apoptotic, atrophic, and inflammatory factors, which might in turn induce sarcopenia mediated by muscle cell senescence ( Alcalde-Estévez et al, 2020 ; Mijares et al, 2021 ; Moustogiannis et al, 2021 ).…”
Section: Senescence In Skeletal Musclementioning
confidence: 99%
“…Several potential mechanisms of muscle cell senescence–mediated, aging-associated muscle loss (sarcopenia) were proposed based on an in vitro study using C2C12 cells, a murine myoblast cell line ( Alcalde-Estévez et al, 2020 ; Mijares et al, 2021 ; Moustogiannis et al, 2021 ). These studies revealed that elevated intracellular Ca 2+ concentration or endothelin-1 receptor in C2C12 cells induces cellular senescence, and senescent C2C12 cells increase the expression of apoptotic, atrophic, and inflammatory factors, which might in turn induce sarcopenia mediated by muscle cell senescence ( Alcalde-Estévez et al, 2020 ; Mijares et al, 2021 ; Moustogiannis et al, 2021 ). On the other hand, recent in vivo analysis of human skeletal muscle revealed that there is no difference in the abundance of γH2AX-positive myonuclei between young individuals (21–30 years old) and old individuals (70–86 years old) ( Dungan et al, 2020 ).…”
Section: Senescence In Skeletal Musclementioning
confidence: 99%
“…On the other hand, mechanical loading can have beneficial or detrimental effects on differentiated cardiomyocytes, depending on its specific characteristics [29], by activating pro-inflammatory factors, such as IL-1β, TNF-α, IL-6, and NF-kB, as well as muscle atrophy and pro-apoptotic factors, such as myostatin, muscle-specific ubiquitin ligase Atrogin-1 (MaFbx), FoxO1, and p53, which have been negatively implicated in cell growth and survival, inducing cardiac muscle wasting and promoting heart failure [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%